Diminishing Returns and the Relative Share of Labor - Marty, Alvin L. (Quarterly Journal of Economics, 1953)
Journal Article Diminishing Returns and the Relative Share of Labor Get access Alvin L. Marty Alvin L. Marty University of California, Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 67, Issue 4, November 1953, Pages 615–618, https://doi.org/10.2307/1883608 Published: 01 November 1953